Theater and Popular Cultures:: contributions by researcher Beti Rabetti to discussions on the subject - Ferreira da Rocha Junior, Alberto (Revista Brasileira de Estudos da Presença, 2023)
This article aims to discuss the contribution of Beti Rabetti (Maria de Lourdes Rabetti) to discussions on the relation between theater and popular cultures. A brief overview of the researcher’s career and discussions on the subject are presented, based on her research work and publications, and on her work as an advisor, focusing on her discussion on the importance of the modes of theatrical production. Popular culture is discussed from authors such as Bakhtin, Burke, Canclini and José Jorge de Carvalho. Aspects of popular comic theater, teatro de revista in Brazil and manifestations of traditional cultures in their relations with the theater of Ariano Suassuna are also discussed.